Proklos : Methode, Seelenlehre, Metaphysik : Akten der Konferenz in Jena AM 18.-20. September 2003 - Perkams, Matthias.; Piccione, Rosa Maria. (Philosophia Antiqua, 2006)
This volume deals with the philosophy of Proclus, the most influential philosopher of the Neoplatonic school of Athens. Its 17 essays present the major themes of Proclus' work. The first part discusses the method of Proclus' philosophy, concentrating on his theory of language and his interpretation of Plato. The second part focusses on his theory of the soul, especially of the human soul and its various functions. The third part covers Proclus' metaphysics, his theory of ideas and his famous scheme of duration, procession and reversion. Thus, the volume contributes to the renewed interest in Neoplatonism. For the specialists, it contains some new insights into Proclus' thought. For the non-specialist, the volume can be used as introductory text to the main themes of Proclean philosophy.